Manure Composting for Small Horse Farms - Erika Sakers; Mary G. Lusk; Carissa Wickens; Caitlin Bainum (EDIS)
The purpose of this new 5-page publication of the UF/IFAS Department of Soil, Water, and Ecosystem Sciences is to present the benefits of composting horse manure on small farms and to provide guidance on how to implement manure composting. This article, the first in a two-part series, is intended for recreational horse enthusiasts managing equine on small (<20 acre) farms. Written by Erika Sakers, Mary G. Lusk, Carissa Wickens, and Caitlin Bainum. https://edis.ifas.ufl.edu/ss709